FIELD ASSESSMENT OF ROCK STRENGTH BY IMPACT LOAD TEST (Malaysian Journal of Civil Engineering, 2018)
This paper introduces a new testing method for field determination of Index strength of rock mass. The method was developed as an alternative test in cases when difficulties were encountered by conventional Schmidt Hammer to determine the index strength of weak or weathered rock. This note explains the basic concept and the procedure of impact load test as an alternative way to determine the index strength of weak or highly weathered rock. A standard chart was developed for interpretation of impact load test through verification study on weathered granite.